Parent and Provider Perspectives on the Diagnosis and Management of Autism in a Chinese Immigrant Population. Issue 4 (May 2019) - Sakai, Christina; Mulé, Christina; LeClair, Amy; Chang, Frances; Sliwinski, Samantha; Yau, Yoyo; Freund, Karen M.
ABSTRACT: Objective: Minority families experience disparities in the diagnosis and management of autism spectrum disorder (hereafter "autism"). To date, the experiences of Chinese immigrant families in the United States have not been explored. Utilizing parent and provider perspectives, this research sought to identify barriers and facilitators to the diagnosis and management of autism among Chinese immigrant children. Methods: We conducted semistructured qualitative interviews with 16 parents of Chinese children diagnosed with autism and 16 providers who assist in the diagnosis and management of autism. Participant characteristics were analyzed utilizing descriptive statistics. Interviews were audiorecorded, transcribed, translated, and independently coded by 2 researchers until consensus was reached. Coded data were analyzed using a modified grounded therapy approach. Results: Parents and providers both identified cultural beliefs as an influence on the understanding and acceptance of autism as a diagnosis. There was a high degree of alignment in themes related to barriers to health care access and parent-provider communication. Recommendations to improve the system of care include (1) supporting communication, (2) cultural sensitivity, and (3) care coordination programming. Conclusion: Findings reinforce that diagnosis and treatment of autism should take into account culturally specific beliefs about child developmental norms and should address systems-, provider-, and family-level barriers.